Vanadium-based highly active and selective catalysts for oxidative dehydrogenation of ethyl lactate to ethyl pyruvate - Doke, Dhananjay; Khomane, Sonali B.; Pandhare, Swati; Dongare, Mohan K.; Dumeignil, Franck; Umbarkar, Shubhangi (Applied Catalysis A: General, 2019)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Pyruvates are important intermediates for various bioactive and pharmaceutical molecules. Synthesis of pyruvates is challenging due to low selectivity, as the pyruvates are prone to polymerisation. In the present work, oxidative dehydrogenation of ethyl lactate to ethyl pyruvate was carried out under very mild conditions using vanadium-based homogeneous and heterogeneous catalysts in the presence of aqueous <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">t<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">-butyl hydroperoxide as an oxidant. Homogenous vanadium-based catalyst, VO(acac)<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> in acetonitrile solvent, gave excellent conversion (upto 83%) with 100% selectivity to ethyl pyruvate at room temperature. However, the heterogeneous catalyst, V<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> exhibited very high activity for oxidative dehydrogenation of ethyl lactate only at higher temperature (80 °C). At higher temperature, significant TBHP decomposition was observed if all TBHP was added in one lot. In case of ethyl lactate dehydrogenation using V<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> catalyst at 80 °C with two equivalents TBHP, 60% ethyl lactate conversion with 100% TBHP conversions were observed after 5 h when all TBHP was added initially in the reaction mixture. However, the ethyl lactate conversion at 80 °C, after 5 h increased to 72% when the same amount of TBHP was added batch wise over a period of 4 h, indicating improved conversion of TBHP to ethyl pyruvate. The heterogeneous catalyst, V<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> exhibited up to 98% conversion with 100% ethyl pyruvate selectivity at 80 °C after 10 h with 3 equivalent TBHP added batch wise. The homogeneous catalyst could not be reused while V<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> could be successfully recycled five times without catalytic performances loss. Oxidation proceeds by radical mechanism, as proved by experiment with radical scavenger.